A new semiconducting 1D Cu(i)–Cu(ii) mixed-valence coordination polymer with Cu(ii) dimethylpiperidine–dithiocarbamate and a tetranuclear Cu(i)–Br cluster unit. (23rd February 2018) - Himoto, K.; Suzuki, S.; Okubo, T.; Maekawa, M.; Kuroda-Sowa, T.
Abstract : A new 1D semiconducting mixed-valence Cu(i )–Cu(ii ) coordination polymer was synthesized and characterized using impedance measurements. Abstract : A novel mixed-valence coordination polymer [CuI4Cu II Br4 (dmpip-dtc)2 (CH3 CN)] n (dmpip-dtc = dimethylpiperidine–dithiocarbamate) with an infinite one-dimensional structure was synthesized and structurally characterized using X-ray diffraction. The electronic properties of the coordination polymer were investigated by UV-vis-NIR spectroscopy. Impedance measurement results demonstrated that this complex has a narrow bandgap, inducing semiconducting behavior.